Urban Sanitation Experiences of Senegal and Burkina Faso : Broadening Urban Sanitation Activities - World Bank (Washington, DC, 2013)
This study aims to offer evidence that urban sanitation in large West African cities faces specific issues linked to urban setting, housing development and urban environment, and to the development of water services. These issues are acutely perceived by urban households and largely shape their demand for sanitation, whereas the available supply offers unsatisfactory or unaffordable solutions. The two operations in review showed that public sanitation (or water and sanitation) utilities, when supported by a strong political will and with the assistance of a variety of actors, may, to a large extent, fill the gap between supply and demand, provided that they adopt adequate and efficient implementation arrangements in a participatory approach. As importantly, both operations showed that cost-effectiveness and equity considerations justify substantial subsidies for household facilities, which can be sustained by internal resources and external assistance. Structure of this report: section one review the trends of the urban sanitation market in West Africa and the rationale for public interventions in sanitation. Section two summarizes the main design features of the two operations. Section three assesses the operations' performances, in terms of outcome, efficiency and equity as well as their sustainability and replicability.